2012
DOI: 10.1038/jid.2011.415
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Meta-Analysis of Psoriatic Arthritis Identifies Susceptibility Locus at REL

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory musculoskeletal disease affecting up to 30% of psoriasis vulgaris (PsV) cases and approximately 0.25% to 1% of the general population. To identify common susceptibility loci, we performed a meta-analysis of three imputed genome-wide association studies (GWAS) on psoriasis, stratified for PsA. A total of 1,160,703 SNPs were analyzed in the discovery set consisting of 535 PsA cases and 3,432 controls from Germany, the United States and Canada. We followed up tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 38 publications
1
64
0
1
Order By: Relevance
“…Because 80% of the patients develop PsA following psoriasis (Ellinghaus et al 2012b), PsA is sometime considered as a disease within a disease (Eder et al 2011). In keeping with this, several PsA susceptibility genes, such as HLA-C, IL-12B, IL-23R, TNIP1 overlap with psoriasis (Liu et al 2008;Huffmeier et al 2010;Ellinghaus et al 2012b).…”
Section: Psoriatic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Because 80% of the patients develop PsA following psoriasis (Ellinghaus et al 2012b), PsA is sometime considered as a disease within a disease (Eder et al 2011). In keeping with this, several PsA susceptibility genes, such as HLA-C, IL-12B, IL-23R, TNIP1 overlap with psoriasis (Liu et al 2008;Huffmeier et al 2010;Ellinghaus et al 2012b).…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…In keeping with this, several PsA susceptibility genes, such as HLA-C, IL-12B, IL-23R, TNIP1 overlap with psoriasis (Liu et al 2008;Huffmeier et al 2010;Ellinghaus et al 2012b). On the other hand, differences in the genetic background of the two conditions do exist and unique genetic determinants have been identified, although not at genome-wide significance (Liu et al 2008).…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…SNPs in STAT3 have been linked to many of the same human autoimmune diseases associated with the IL-23 pathway, including psoriasis, IBD, and ankylosing spondylitis (66)(67)(68). Loss-of-function mutations in STAT3 lead to the development of autosomal-dominant hyper-IgE syndrome, manifestations of which include chronic mucocutaneous candidiasis and recurrent staphylococcal infections.…”
Section: Cytokine Regulation Of Th17 Differentiationmentioning
confidence: 99%
“…Our understanding of the genetic architecture of psoriasis has increased rapidly due to genome-wide association studies (GWASs), which have identified more than 40 psoriasis susceptibility genes/loci [2][3][4][5][6][7][8][9][10][11][12][13] . However, the combined effect of these loci does not fully account for the observed genetic susceptibility to psoriasis, indicating that additional genetic factors remain to be discovered.…”
mentioning
confidence: 99%